2021
DOI: 10.1242/jeb.242393
|View full text |Cite
|
Sign up to set email alerts
|

Larval nutrition impacts survival to adulthood, body size and the allometric scaling of metabolic rate in adult honeybees

Abstract: Resting metabolic rate (RMR) is a fundamental physiological measure linked to numerous aspects of organismal function, including lifespan. Although dietary restriction in insects during larval growth/development affects adult RMR, the impact of the nutritional composition of larval diets (i.e. diet quality) on adult RMR has not been studied. Using in vitro rearing to control larval diet quality, we determined the effect of dietary protein and carbohydrate on honeybee survival to adulthood, time to eclosion, bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 87 publications
(108 reference statements)
0
13
1
Order By: Relevance
“…Glutamic acid only increased the survival of the total bee brood when added to the standard diet. The larval diet composition of honey bees affects the developmental period and survival of immature bees to adults (Nicholls et al, 2021). Our results did not agree with earlier studies that showed higher mortalities of larvae (Helm et al, 2017) and adult (Pirk et al, 2010) bees when fed on a diet with higher protein concentrations.…”
Section: Discussioncontrasting
confidence: 99%
“…Glutamic acid only increased the survival of the total bee brood when added to the standard diet. The larval diet composition of honey bees affects the developmental period and survival of immature bees to adults (Nicholls et al, 2021). Our results did not agree with earlier studies that showed higher mortalities of larvae (Helm et al, 2017) and adult (Pirk et al, 2010) bees when fed on a diet with higher protein concentrations.…”
Section: Discussioncontrasting
confidence: 99%
“…Diet represents the most important environmental factor for animal survival, growth, reproduction, and various other physiological traits. In many oviparous insects, the developmental diet of immature stages (e.g., larvae) is determined by the mother's egg-laying site selection ( Björkman et al., 1997 ; Fortuna et al., 2013 ; Gripenberg et al., 2010 ), which could also shape their long-term performance and life-history phenotypes ( Langley-Evans, 2015 ; Nicholls et al., 2021 ; Stefana et al., 2017 ). The preference-performance (“mother knows best”) hypothesis assumes maternal oviposition preference evolves toward maximizing offspring fitness ( Jaenike, 1978 ).…”
Section: Introductionmentioning
confidence: 99%
“…This may help explain the differences observed in male body size trends between C. pallida (where this is not the case) and the other studied species in Oliveira et al (2016). Low quantity or quality larval nutrition significantly reduces survival and impacts adult physiology (Lawson et al 2020, Nicholls et al 2021, resulting in reduced mating and foraging success (Muller et al 2015, Xie et al 2015. The negative fitness consequences of small body sizes may cause a species-specific lower bound on resource allocation per offspring.…”
Section: Discussionmentioning
confidence: 96%